Dominance of candidate Saccharibacteria in a membrane bioreactor treating medium age landfill leachate: Effects of organic load on microbial communities, hydrolytic potential and extracellular polymeric substances. (August 2017) - Remmas, Nikolaos; Melidis, Paraschos; Zerva, Ioanna; Kristoffersen, Jon Bent; Nikolaki, Sofia; Tsiamis, George; Ntougias, Spyridon
Highlights: Organic load, salinity and NH4 + -N influenced EPS and SMP during leachate treatment. Exceptionally high β -glucosidase activities were determined during MBR operation. Candidate Saccharibacteria were dominant at any landfill leachate concentration. A massive shift in other bacterial taxa was observed at high organic loading rate. The new fungal phylum Cryptomycota was predominant at high organic loading rate. Abstract: A membrane bioreactor (MBR), accomplishing high nitrogen removal efficiencies, was evaluated under various landfill leachate concentrations (50, 75 and 100% v/v). Proteinous and carbohydrate extracellular polymeric substances (EPS) and soluble microbial product (SMP) were strongly correlated ( p  <  0.01 ) with organic load, salinity and NH4 + -N. Exceptionally high β- glucosidase activities (6700–10, 100 U g −1 ) were determined during MBR operation with 50% v/v leachate, as a result of the low organic carbon availability that extendedly induced β- glucosidases to breakdown the least biodegradable organic fraction. Illumina sequencing revealed that candidate Saccharibacteria were dominant, independently of the leachate concentration applied, whereas other microbiota (21.2% of total reads) disappeared when undiluted leachate was used. Fungal taxa shifted from a Saccharomyces - to a newly-described Cryptomycota-based community with increasing leachate concentration. Indeed, this is the first report on the dominance of candidate Saccharibacteria and on the examination of their metabolic behavior in a bioreactor treating real wastewater.